Web-Based Monitoring and Management System for Livestock Operations - Firdaus, Ananda Ade (PT. Lentera Ilmu Publisher, 2025)
Monitoring livestock health and productivity is a critical aspect of agricultural management, yet many organizations still rely on manual or disconnected systems that lead to inefficiencies, delayed reporting, and lack of real-time insight. These challenges hinder timely decision-making, especially in identifying diseases, recording births and deaths, and maintaining accurate data. To address this gap, this study introduces a Web-Based Livestock Monitoring System designed to streamline data entry, enable centralized access, and support role-based interaction for Admins, Livestock Staff, and the Head of Department. The system was developed using a structured web application model, with core features including user authentication, livestock categorization, health monitoring, and monthly report generation. A black-box testing approach was used to evaluate its functionality from the user's perspective without delving into internal code logic. Testing results showed that all features—such as login validation, data input, and report generation—operated successfully and provided the expected outputs. This system offers a practical solution for modernizing livestock monitoring processes, enhancing efficiency, data accuracy, and communication across roles. It contributes to more effective livestock management by ensuring that health data is up-to-date and accessible, allowing stakeholders to make informed decisions and respond proactively to issues in the field.